ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI ATTITUDINAL LOYALTY DAN BEHAVIORAL LOYALTY PADA NASABAH PERBANKAN SYARIAH - Wulandari, Deasy (IQTISHODUNA, 2012)
Bank Muammalat Indonesia (BMI) as a leading banking in the syariah system should improve their service quality to the customers and know the customers based brand equity to keep their loyalty and competitive advantages. This research is held to test the influences service quality and brand equity toward the customers loyalty. SEM is used as the technic of analysis. The five hypothesis proposed is accepted. The management should give time more to value every single indicator variable in order to keep and improve the customer loyalty. Â